Atrial High‐Rate Episode Duration Thresholds and Thromboembolic Risk: A Systematic Review and Meta‐Analysis - Dimitrios Sagris (Wiley, 2021)
Background Available evidence supports an association between atrial high‐rate episode (AHRE) burden and thromboembolic risk, but the necessary extent and duration of AHREs to increase the thromboembolic risk remain to be defined. The aim of this systematic review and meta‐analysis was to identify the thromboembolic risk associated with various AHRE thresholds. Methods and Results We searched PubMed and Scopus until January 9, 2020, for literature reporting AHRE duration and thromboembolic risk in patients with implantable electronic devices. The outcome assessed was stroke or systemic embolism. Risk estimates were reported as hazard ratio (HR) or relative risk alongside 95% CIs. We used the Paule‐Mandel estimator, and heterogeneity was calculated with I2 index. Among 27 studies including 61 919 patients, 23 studies reported rates according to the duration of the longest AHRE and 4 studies reported rates according to the cumulative day‐level AHRE duration. In patients with cardiac implantable devices, AHREs lasting ≥30 seconds significantly increased the risk of stroke or systemic embolism (HR, 4.41; 95% CI, 2.32–8.39; I2, 5.5%), which remained consistent for the thresholds of 5 minutes and 6 and 24 hours. Patients with previous stroke or transient ischemic attack and AHREs lasting ≥2 minutes had a marginally increased risk of recurrent stroke or transient ischemic attack. The risk of stroke or systemic embolism was higher in patients with cumulative AHRE ≥24 hours compared with those of shorter duration or no AHRE (HR, 1.25; 95% CI, 1.04–1.52; I2, 0%). Conclusions This systematic review and meta‐analysis suggests that single AHRE episodes ≥30 seconds and cumulative AHRE duration ≥24 hours are associated with increased risk of stroke or systemic embolism.